Relationship commitment and motive congruence : the key to battling infidelity? - Lo, Dion Zhen Yu (2014)
Infidelity is a form of relational transgression that has severe negative consequences for intimate relationships. Considering the negative ramifications associated with infidelity, many researchers have investigated its possible causes, hoping to reduce unfaithful acts. The majority of these studies have however, only looked at actual unfaithful behaviours. Few, if any, studies examined individuals’ attitudes towards infidelity. A person who has positive attitudes towards infidelity would have higher potential in committing infidelity as compared to one who has negative attitudes towards infidelity. Given that an individual’s attitudes can strongly influence one’s actual behaviour, investigating predictors that influence an individual’s attitudes towards infidelity will be useful in the prevention of actual infidelity acts. Relationship commitment and motive congruence have emerged in the literature as factors that are related to positive relationship outcomes. In view of these, the current research examined the effect of relationship commitment and motive congruence on individuals’ attitudes towards infidelity. Specifically, a manipulation procedure was employed to categorize participants into high vs. low relationship commitment group. The high commitment group was expected to report more negative attitudes towards infidelity than the low commitment group. The congruence between implicit and explicit need for affiliation (Affiliation motive congruence) was expected to moderate the association between commitment and infidelity. Regression analyzes revealed the predicted pattern of results for relationship commitment but not for affiliation motive congruence. Results suggest positive implications for future interventions.